Teaching the art of living is a bet to educate the future according to the open vision of Edgar Morin. - gargui, imen (Journal of Social Sciences and Humanities, 2023)
This article aims to explain the etiquette and arts of living, in order to prepare for life, according to the open-view perspective, "Edgar Moran" who emphasized that the concepts of "the art of living", "living and dignified" and "etiquette of life" should be included in the educational system, as everyone must be taught How to live in order to face all the crises and dangers facing it, as Moran considers that teaching the art of living is subject to education in the future in order to keep pace with the reform of life, complementing the reform of thought and knowledge, in order to get out of the crises and pain that Western civilization has generated in all, especially in the field of understanding The complications of living and their causes.